Video analysis in Design-Based Research - Findings of a project on self-organised learning at a vocational school - Gössling, Bernd [Verfasser]; Daniel, Desiree [Verfasser] (My University, 2018)
"The use of video analysis in Design-Based Research (DBR) seems to be promising, because the quality of video data matches the reality of educational fields. Educational fields are multidimensional and complex. And more than other types of data, video may capture, for example, the simultaneity of verbal and non-verbal interactions. This seems to be valuable in the quest for new insights and better designs of educational interventions. However, to date there has been limited use of video data in researching their design. This paper aims at reflecting how the benefits of video-based analysis may be utilised in DBR. Experiences with the collection and analysis of video data in a project to design self-organised learning (SOL) at a vocational school in Germany will be used as a case study to illustrate the type of findings that may feed into the DBR process. In this case, the project school had already introduced a sophisticated SOL model but was experiencing various implementation difficulties. Resolving issues like this requires insights into how exactly a concept is realised and what happens in the field. Therefore, video data on classroom interactions was gathered and sub-sequently analysed using the documentary method. This led to the reconstruction of two different types of orientation that were guiding the students when they dealt with their self-organised learning environment. In a subversive orientation, students playfully infiltrate the formal learning space with peer activities. In a confirming orientation, students stick to both, the (informal) rules of the (formal) learning arrangement and of the peer environment, thus expressing respect for the boundary between these two worlds. These findings have been used to redesign the SOL intervention." (Authors' abstract, BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; T 3 Forschungsmethoden; L 2.1 Lernformen; S 3.1.2.1 Berufliche Teilzeitschulen, Berufsschulen; L 4.1.2 Elektronische Medien; Berufsbildungsforschung; Gestaltungsbasierte Forschung; Forschungsprojekt; Selbstgesteuertes Lernen; Lernort Schule; Berufsschule; Multimediales Lernen; Video